(untitled) (Asian-Australasian Journal of Food Safety and Security, 2020)
Salt-tolerant Boro rice response under the interaction of variety and urea fertilizer was assessed in the southern coastal region of Bangladesh for developing coastal agriculture in Bangladesh. A field experiment was carried out at the research field of Agriculture department, Noakhali Science and Technology University (NSTU), Noakhali-3814 in a Randomized Complete Block Design (RCBD) with two varieties viz. BINA dhan-8, BRRI dhan-67 and three doses of urea viz. 250 kg/ ha., 150 kg/ ha. and 120 kg/ ha. were used as treatments where each treatment was replicated three times. Data were collected on plant height (cm), tiller/hill, grain/panicle, 1000 grain weight (g), grain yield (t/ha.), straw yield (t/ha.) and harvest index (%). All the parameters were influenced significantly by the interaction of variety and different doses of urea fertilizer and better performance was obtained from the variety BINA dhan-8 and the doses of 250 kg urea/ ha. Finally, the present study suggests that for obtaining higher yield salt-tolerant BINA dhan-8 variety may be cultivated with 250 kg urea/ ha. in the southern coastal region of Bangladesh. Asian Australas. J. Food Saf. Secur. 2020, 4 (1), 1-7